Psychological Stress and Management Strategies for Academic Staff of Tertiary Institutions in Nigeria - Olanrewaju Musa Murtala; Bernice Olohitai Eri; Niyi Jacob Ogunode (Researchparks Publishing, 2022)
This paper discussed stress management strategies for academic staff of tertiary institutions in Nigeria. Both secondary and primary data were employed. Data was collected from print materials and online publications. This study reveals that excess workload, lack of instructional materials, inadequate infrastructural facilities, exorbitant work demands, conflicting roles, pressure towards conformity, job insecurity, strike actions, insecurity and students’ misbehavior are causes of stress among academic staff in tertiary institutions in Nigeria. Consequently, studies of psychological stress hamper environmental events that put people’s ability to cope or individual responses to events that elicit negative affect. In this article, the definition of stress does not include psychiatric disorders linked to stress but is limited to the academic environment. To address these, the paper recommended among other things that the tertiary institutions’ administrators should ensure that capacity building on stress management is organized for the academic staff. This will help to reduce stressors and enhance resilience skills and coping mechanisms among them.